Institutional Governance, Education and Growth - Mohamed Jellal; Bouzahzah Mohamed; Simplice Asongu (African Governance and Development Institute (AGDI), 2015)
This study articulates the interaction between institutional governance, education and economic growth. Given the current pursuit of education policy reforms and knowledge economy around the world, it is of policy relevance to theoretically analyze the main mechanisms by which the macroeconomic impact of education on growth (and economic development) occurs. Our theoretical model demonstrates how incentives offered by the government affect human capital accumulation which ultimately engenders positive economic development externalities. We articulate two main channels through which education affects economic growth. The first channel highlights direct positive effect of educational quality on the incentive to accumulate human capital by individuals, which makes them more productive. The second channel appears in the explicit function of the economic growth rate. As a policy implication, we have shown that the growth rate depends on the rate of return on human capital or that this rate of return itself depends on the quality of governance, which further increases growth. As a result, institutional quality has a double dividend, which suggests considerable benefits to educational reforms.
Keywords: H11; O15; O43; 330; Institutions; Human capital; Education; Growth